التكلفة الفعلية لخدمات الإقراض في المصارف الإسلامية: دراسة تحليلية شرعية = The actual cost of lending services in Islamic banks Shariah: analysis study - Saleh, Abdulmajid Obaid Hasan; noor, Azman Mohd Noor; Abdulbari, Hani Hazai Abdulbari; Al Qassim, Anas Abdulkadir Al Qassim (IIUM Press, 2021)
Shariah councils and bodies permitted taking the actual cost from the lending in Islamic banks, and they based this permissibility on differentiating between the loan and the services accompanying the recovery of the loan and its restrictions, as these actions are excluded from the principal of the loan. However, Islamic banks differed in applying the concept of actual cost between a lump sum or a percentage. Moreover, the shariah bodies differed in the methods of taking this actual cost. Because the fee-based services provided by Islamic banks may bring some Shariah issues related to the imposition of fees or the actual cost. Therefore, this research comes to liberate the actual cost, explain its causes and controls, its root and legal absolutes, and an application model for its reality in Islamic banks. As for the approach used in this study, it is the descriptive and analytical one, by relying on collecting legal texts, then analyzing the doctrines of the jurists and discussing the mechanism for determining the calculation of actual fees and fees from the perspective of Shariah.